Sex differences and determinants of coronary microvascular function in asymptomatic adults with type 2 diabetes - Jian L. Yeo; Abhishek Dattani; Joanna M. Bilak; Alice L. Wood; Lavanya Athithan; Aparna Deshpande; Anvesha Singh; J.Ranjit Arnold; Emer M. Brady; David Adlam; John D. Biglands; Peter Kellman; et al. (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Coronary microvascular dysfunction (CMD) is a significant complication in type 2 diabetes (T2D) and may be more common in women. We aimed to evaluate the sex differences and sex-specific clinical determinants of CMD in adults with T2D without prevalent cardiovascular disease. Methods: Single center pooled analysis of four prospective studies comparing asymptomatic people with T2D and controls. All subjects underwent comprehensive cardiovascular phenotyping with myocardial perfusion reserve (MPR) quantified with perfusion cardiovascular magnetic resonance (CMR). Participants with silent coronary disease were excluded. Multivariable linear regression was performed to identify determinants of MPR with an interaction term for sex. Results: Four hundred and seventy-nine T2D (age 57 ± 11 years, 42% [202/479] women) were compared with 116 controls (age 53 ± 11 years, 41% [48/116] women). Men with T2D, but not women, demonstrated worse systolic function and higher extracellular volume fraction than controls. MPR was significantly lower in T2D than controls (women, 2.6 ± 0.9 vs 3.3 ± 1.0, p < 0.001; men, 3.1 ± 0.9 vs 3.5 ± 1.0, p = 0.004), and lower in women than men with T2D (p < 0.001). More women than men with T2D had MPR <2.5 (46% [79/202] vs 26% [64/277], p < 0.001). There was a significant interaction between sex and body mass index (BMI) for MPR (p interaction <0.001). Following adjustment for clinical risk factors, inverse association with MPR were BMI in women (β = −0.17, p = 0.045) and systolic blood pressure in men (β = −0.14, p = 0.049). Conclusion: Among asymptomatic adults with T2D, women had a greater prevalence of CMD than men. Risk factors modestly but significantly associated with CMD in asymptomatic people with T2D were BMI among women and systolic blood pressure among men.